2012
DOI: 10.1007/s00268-012-1719-5
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Incision Laparoscopic Cholecystectomy Versus Conventional Laparoscopic Cholecystectomy: Meta‐analysis and Systematic Review of Randomized Controlled Trials

Abstract: SILC does not offer any advantage over CLC for treating benign gallbladder disorders. CLC may be used assiduously for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 64 publications
3
45
3
Order By: Relevance
“…[25] Several studies have demonstrated that less postoperative pain is associated with a reduction in either size or number of trocars. [18,19,22,24] However, other studies have claimed that the diminished port technique did not reduce the overall pain score or [1,3,9,20,21,26,27] In the current study, we failed to demonstrate any difference in terms of overall pain score 12 and 24 hours after surgery or in analgesic requirements among the four groups.…”
Section: Discussioncontrasting
confidence: 51%
“…[25] Several studies have demonstrated that less postoperative pain is associated with a reduction in either size or number of trocars. [18,19,22,24] However, other studies have claimed that the diminished port technique did not reduce the overall pain score or [1,3,9,20,21,26,27] In the current study, we failed to demonstrate any difference in terms of overall pain score 12 and 24 hours after surgery or in analgesic requirements among the four groups.…”
Section: Discussioncontrasting
confidence: 51%
“…The present systematic review embraced 30 RCTs 35-64 comparing SILC to MLC in adult patients (N=2411), more than any of the previously published similar reports [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] . Despite the fact that the overall trial quality is "far from ideal", a fairly reasonable evidence-based assessment of SILC is possible.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent meta-analysis comparing LC vs. SILC, 11 randomized controlled trials with 858 patients were analyzed (9). Postoperative pain, complications, LOS, cosmetic score, conversion rate, need for additional port placement, and time to return to normal activities were found to be similar in both groups, while SILC was associated with significantly longer operation times.…”
Section: Discussionmentioning
confidence: 99%